Step * 3 of Lemma Taylor-remainder-as-integral


1. Interval
2. iproper(I)
3. : ℝ
4. a ∈ I
5. : ℝ
6. b ∈ I
7. [rmin(a;b), rmax(a;b)] ⊆ 
8. : ℤ
9. 0 < n
10. ∀F:ℕ(n 1) 2 ⟶ I ⟶ℝ
      ((∀k:ℕ(n 1) 2. ∀x,y:{a:ℝa ∈ I} .  ((x y)  ((F x) (F y))))
       finite-deriv-seq(I;(n 1) 1;i,x.F x)
       (Taylor-remainder(I;n 1;b;a;k,x.F x) a_∫-(F ((n 1) 1) t/r((n 1)!)) t^n dt))
11. : ℕ2 ⟶ I ⟶ℝ
12. ∀k:ℕ2. ∀x,y:{a:ℝa ∈ I} .  ((x y)  ((F x) (F y)))
13. finite-deriv-seq(I;n 1;i,x.F x)
14. Taylor-remainder(I;n;b;a;k,x.F x) a_∫-(F (n 1) t/r((n)!)) t^n dt
15. {x:ℝx ∈ [rmin(a;b), rmax(a;b)]} 
16. {x:ℝx ∈ [rmin(a;b), rmax(a;b)]} 
17. y
⊢ ((F (n 1) x/r((n)!)) y^n) ((F (n 1) y/r((n)!)) y^n)
BY
((Assert (F (n 1) x) (F (n 1) y) BY Auto) THEN RWO "-1" THEN Auto) }


Latex:


Latex:

1.  I  :  Interval
2.  iproper(I)
3.  a  :  \mBbbR{}
4.  a  \mmember{}  I
5.  b  :  \mBbbR{}
6.  b  \mmember{}  I
7.  [rmin(a;b),  rmax(a;b)]  \msubseteq{}  I 
8.  n  :  \mBbbZ{}
9.  0  <  n
10.  \mforall{}F:\mBbbN{}(n  -  1)  +  2  {}\mrightarrow{}  I  {}\mrightarrow{}\mBbbR{}
            ((\mforall{}k:\mBbbN{}(n  -  1)  +  2.  \mforall{}x,y:\{a:\mBbbR{}|  a  \mmember{}  I\}  .    ((x  =  y)  {}\mRightarrow{}  ((F  k  x)  =  (F  k  y))))
            {}\mRightarrow{}  finite-deriv-seq(I;(n  -  1)  +  1;i,x.F  i  x)
            {}\mRightarrow{}  (Taylor-remainder(I;n  -  1;b;a;k,x.F  k  x)
                  =  a\_\mint{}\msupminus{}b  (F  ((n  -  1)  +  1)  t/r((n  -  1)!))  *  b  -  t\^{}n  -  1  dt))
11.  F  :  \mBbbN{}n  +  2  {}\mrightarrow{}  I  {}\mrightarrow{}\mBbbR{}
12.  \mforall{}k:\mBbbN{}n  +  2.  \mforall{}x,y:\{a:\mBbbR{}|  a  \mmember{}  I\}  .    ((x  =  y)  {}\mRightarrow{}  ((F  k  x)  =  (F  k  y)))
13.  finite-deriv-seq(I;n  +  1;i,x.F  i  x)
14.  Taylor-remainder(I;n;b;a;k,x.F  k  x)  =  a\_\mint{}\msupminus{}b  (F  (n  +  1)  t/r((n)!))  *  b  -  t\^{}n  dt
15.  x  :  \{x:\mBbbR{}|  x  \mmember{}  [rmin(a;b),  rmax(a;b)]\} 
16.  y  :  \{x:\mBbbR{}|  x  \mmember{}  [rmin(a;b),  rmax(a;b)]\} 
17.  x  =  y
\mvdash{}  ((F  (n  +  1)  x/r((n)!))  *  b  -  y\^{}n)  =  ((F  (n  +  1)  y/r((n)!))  *  b  -  y\^{}n)


By


Latex:
((Assert  (F  (n  +  1)  x)  =  (F  (n  +  1)  y)  BY  Auto)  THEN  RWO  "-1"  0  THEN  Auto)




Home Index